Between Solidarity and Anomie: A Study of a Collaboration With a Pooled Budget - Villaume Silberstein, Anna; Eklöv Alander, Gunilla; Holmgren Caicedo, Mikael (Scandinavian Journal of Public Administration, 2025)
While collaboration is often promoted as a solution to complex societal challenges, the role of management accounting tools in facilitating these efforts remains a source of ongoing contention. By drawing on 29 interviews, this study examines a coordination association (samordningsförbund in Swedish) composed of public organizations that jointly fund rehabilitation measures to combat long-term unemployment. The study shows how the pooled budget functions as a ground for collaboration by creating financial interdependence and enabling coordination, communication, and shared practices. While this formalized structure fosters stability, it is also prone to anomic tendencies such as disengagement and short-termism. These tendencies undermine collaboration unless actively countered by practices that promote mutual understanding, shared goals, and practical coordination strategies. Ultimately, effective management accounting in collaborations appears to require not only external enforcement but also internal commitment shaped by the collaboration’s own dynamics and values.